Eco-tourism in Andhra Pradesh - Athma, Prashanta; Lakshmi, Vijaya (Indian Journal of Marketing, 2006)
Tourism plays a major role in the growth of an economy. The tourism industry generates large-scale employment and is also a large foreign exchange earner. The industry is the third largest foreign exchange earner in the country after jewellery and ready-made garments. The most popular destinations among domestic as well as foreign tourists include Hyderabad, Tirupati followed by Visakhapatnam, Vijayawada, Puttaparthi, and Srisailam etc. Hyderabad and Visakhapatnam airports are to be expanded to receive international flights. Hyderabad has been identified as one of the five locations in the country for the establishment of a full-fledged international airport. Direct flights to Singapore, Malaysia have recently commenced from Hyderabad in addition to other destinations. Hyderabad is being developed as a major transit hub between Europe and the Far East.